The movie star mystery - Sturk, Karl; Duendes Del Sur (Firm) (New York : Scholastic, 2009)
Scooby and the gang investigate who stole the list of winners at a Hollywood awards show.
Keywords: Scooby-Doo (Fictitious character); Detective and mystery stories